Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.7861/clinmedicine.4-2-173
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte homing in the pathogenesis of extra-intestinal manifestations of inflammatory bowel disease

Abstract: -Inflammatory bowel disease is associated with extra-intestinal manifestations which occur either at the same time as flares of bowel inflammation (skin and eye disease) or run a course that is independent to inflammation in the bowel (liver and some joint syndromes). It has been suggested that the skin and eye complications occur as a consequence of the recruitment of activated effector cells released from the gut into the circulation to extra-intestinal site where they cause acute damage. However, this does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 21 publications
2
43
0
3
Order By: Relevance
“…33,34 Much effort has been focused on determining specific molecular mechanisms responsible for immune cell mediated tissue damage during colitis. Several reports have previously identified leukocyte and endothelial cell adhesion molecules as potentially important regulators of leukocyte recruitment in human IBD and experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Much effort has been focused on determining specific molecular mechanisms responsible for immune cell mediated tissue damage during colitis. Several reports have previously identified leukocyte and endothelial cell adhesion molecules as potentially important regulators of leukocyte recruitment in human IBD and experimental colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Such an inability of the liver to control activation of memory/ effector T cells is particularly interesting in situations where these T cells are recruited to the liver and have been shown to produce local organ damage. 32,33 However, cytokines released from NKT and T cells after a single application of aCD3eAb did not lead to local inflammation in the liver, because no alanine aminotransferase increase or histological evidence of liver damage was observed (data not shown). However, local release of cytokines exerted antiviral effects in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the liverinfiltrating lymphocytes in PSC include mucosal T cells recruited to the liver by aberrant expression of the gutspecific chemokine CCL25 that activates α4/β7 binding to MAdCAM-1 on the hepatic endothelium (63,68). Therefore, targeting the CCL25-MAdCAM-1 axis could be of therapeutic benefit in PSC.…”
Section: Monoclonal Antibodies and Pscmentioning
confidence: 99%
“…M u c o s a l a d r e s s i n c e l l a d h e s i o n m o l e c u l e 1 (MAdCAM-1), an endothelial cell adhesion molecule, is expressed in high amounts in the gut of patients with IBD and those with IBD and PSC (62)(63)(64)(65). Vascular adhesion protein 1 (VAP-1) has been found to induce the expression of MAdCAM-1 in the hepatic endothelial cells of human liver tissue (66).…”
Section: Monoclonal Antibodies and Pscmentioning
confidence: 99%